The predictive value indicators of first trimester biochemical screening in assessing unfavorable factors of pregnancy course in women with HIV as well as hepatitis B and C - S. Yu. Pseush; L. V. Zozulya; L. L. Mikhaleva (Акушерство, гинекология и репродукция)
Aim: to find out the predictive value of blood serum biochemical parameters PAPP-A (pregnancy-associated plasma protein A) and β-hCG (beta subunit of human chorionic gonadotropin) in the assessment of unfavorable pregnancy outcomes in women infected by human immunodeficiency virus (HIV) as well as viral hepatitis B (HBV) and C (HCV).Materials and Methods. A retrospective study of the medical records from 52 women was carried out, including 19 HIV-infected women, 9 women with monoinfection HBV or HCV, 11 pregnant women who were co-infected (HIV/HBV or HIV/HCV) and 13 uninfected women. PAPP-A and β-hCG levels, expressed as MoM (multiple of median), were evaluated in all women.Results. Our study revealed that only PAPP-A was prognostically significant for developing chronic placental insufficiency in women with HIV infection and co-infection of HIV together hepatitis B and C. None of the parameters examined were significant in women with HBV or HCV monoinfection. PAPP-A and β-hCG in pregnant women without infections were effective in predicting development of chronic placental insufficiency.Conclusion. PAPP-A can be used as a diagnostic parameter of developing chronic placental insufficiency in pregnant women with monoinfection HIV and co-infection with HIV/HBV or HIV/HCV.